Asociación entre anemia y rendimiento académico en el preescolar en la I.E. N° 81514 Francisco Bolognesi de Casa Grande durante el año 2016 - Palomino Castañeda, Yonel Alexander (2018)
To determine the association of anemia and its impact on academic performance in preschool children. Academic performance is the student's achievement of the educational goals pre-programmed in a conventional manner for their age. Materials and methods: A descriptive, cross-sectional investigation was carried out with a non-experimental correlational design. 56 preschoolers, both genders, whose ages ranged between 3 and 5 years, were evaluated during the 2016 academic year. A data collection form was used and statistical calculations were carried out with the statistical program Windows SPSS version 24. Results: 42.9% of the total of preschool children presented anemia. Academic Performance: Mathematics (A = 44.6%, B = 50%, C = 5.4%); Communication / Art (A = 46.4%, B = 46.4%, C = 7.1%); Social Personnel / Religion (A = 76.8%, B = 23.2%, C = 0%); Science and Environment (A = 55.4%, B = 42.9%, C = 1.8%). A statistically significant difference (p <0.05) was observed among preschoolers with anemia and poor school performance. Conclusions: There is a positive and inverse correlation between low academic performance and the presence of anemia in the preschool children evaluated